Study of the genus Sobrina Ach. (liehenized Ascomycetes) in tite Iberian Peninsula - Burgaz Moreno, Ana Rosa; Martínez Moreno, Isabel (Botanica Complutensis, 1998)
BURGAZ, A. R. & MARTÍNEZ, 1. 1998. Study of the genus Sobrina Ach. (¡ichenized Ascomycetes) in the Iberian Peninsula. BoL Complutensis 22: 63-73. Ihe morphologic-al, chorological and ecological characteristies of ifie fmve taxa of the genus Sobrina growing in the Iberian Peninsula are reported. Distribution maps of each taxa are included. 1(ey words: Chorology, ecology, maps, Sobrina.